Aktuelle Aussprachewörterbücher des Deutschen und des Englischen im Vergleich - Nycz, Krzysztof; Tęcza, Zygmunt (Lexikos, 2025)
Current Pronunciation Dictionaries of German and English Compared. The following paper takes a critical and comparative look at a total of five dictionaries of pronunciation, two German and three English, which represent the current state of development in German and English phono-lexicography. The aim of this comparison is not only to discuss the advantages and disadvantages of the individual works in the context of current lexicographical practice and, possibly, to provide ideas for future developments in presenting and conveying pronunciation information, but also to stimulate an interlingual discourse that could contribute to reflection on universal and language-specific challenges in phonetic standardisation and codification. As a starting point, a general description of the dictionaries under investigation is provided, covering aspects such as their origins, target groups, as well as the construction and extent of the respective word lists and front matters. The actual analysis focuses on four main areas: the concept of what is to be considered and codified as standard pronunciation, the treatment of phono-stylistic and regional pronunciation variants, the graphic design of the dictionaries compared, and finally their multimedia extensions. The last section summarises the similarities and, above all, the differences between the dictionaries analysed in the above areas, and concludes with a brief subjective outlook on the future prospects of pronunciation dictionaries. Keywords: pronunciation dictionary, pronunciation codification, German pronunciation, English pronunciation, standard pronunciation, phonetic standard, pronunciation variants, phono-lexicography, digital lexicography, electronic lexicography